Are Patients With Fibromyalgia in a Prothrombotic State?. Issue 2 (March 2019) - Molina, Francisco; del Moral, María Luisa; La Rubia, Mercedes; Blanco, Santos; Carmona, Ramón; Rus, Alma
Objectives: The aim of this study was to investigate thrombosis-related parameters (blood coagulation parameters, platelet indices, red blood cell [RBC] count, and inflammatory markers) in patients with fibromyalgia (FM). Method: We carried out a case–control study with 35 women with FM and 12 age-matched healthy volunteers to analyze fibrinogen levels, prothrombin time, cephaline time, platelet count, platelet distribution width (PDW), mean platelet volume (MPV), RBC count, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio (PLR). Results: The results showed significantly increased fibrinogen levels ( p < .05), platelet count ( p < .05), PDW ( p = .059), RBC count ( p < .05), and PLR ( p < .05) in women with FM versus the healthy volunteers. Prothrombin time ( p < .05) and MPV ( p < .05) were significantly lower in patients with FM than in the controls. Conclusions: Elevated platelet and RBC counts, PDW values, and fibrinogen levels as well as decreased prothrombin time are all indicative of a prothrombotic state in FM patients, which may be enhanced by an increased inflammatory tone. This prothrombotic state may increase the risk of thrombosis-related cardiovascular disease in patients with FM.